Clima urbano em cidade de pequeno porte : estudo de caso em Campo Novo do Parecis-MT - Mello, Vergínia Rodrigues de (2024)
The study of urban climate becomes necessary as changes are detected in the daily life of a society, not only in large centers but also in medium and small cities. Such changes can compromise the environmental quality and quality of life of the population, processes that also affect the economic and social aspects of the space. In this sense, the importance of analyzing the urban climate in Campo Novo do Parecis-MT is highlighted, as it is unprecedented research for the municipality. Thus, the objective was to investigate and analyze the urban climate, especially regarding its thermal field (Channel I: thermal comfort, thermodynamic subsystem, of the Urban Climate System proposed by Monteiro, 1976) as it is from this field that the climatic characteristics of cities are configured. The search for information through the framework of renowned researchers, the development of maps characterizing the location, and, when combined with fieldwork using the mobile transect, data collection from fixed points scattered throughout the city and rural surroundings provided support for the analysis of the urban climate and how social action has been influencing the geographical space of Campo Novo do Parecis-MT. Data from fixed points during the dry season were compared and analyzed with the rainy season. From the records of mobile transects, islands of weak, moderate, strong, and very strong heat magnitude were observed during the dry season, while during the rainy season, heat islands of weak and moderate magnitude were identified, characterizing the central area as the hottest region in the urban space, highlighting the need for a closer look at the urban planning of the municipality Campo Novo do Parecis-MT.